EFFECTS OF STRESS–BUFFERING, JOB RESOURCES ON PSYCHOLOGICAL WELL-BEING WITH HEALTH AS A MODERATING VARIABLE TO HEALTH PROFESSIONALS AT HOSPITAL X - Jurita Purnama Sari; Wahyuni Dian; Rina Anindita (Jurnal Cinta Nusantara, 2024)
Psychological well-being is a core element of overall well-being and is connected to physical health, mental health. Work does not only involve risk factors and stressors, but also provides protective factors and resources (job resources) that help to buffer stress (stress buffering). In general, this study aims to determine the effect of stress buffering, job resources and health on the psychological well-being of health professionals. This research is included in the cross-sectional study. In this study also used a quantitative descriptive approach, the selected population was all health professionals working at the Hospital X, totalling 100 people. Data collection was done by distributing questionnaires. There are two independent variables, namely stress buffering (X1) and job resources (X2), one intervening variable, namely health (Z) and one dependent variable, namely welfare (Y). Based on the t test, there is an effect of the Stress Buffering variable on Psychological Well-being of p=0.004. There is an effect of health on psychological well-being p=0.001. There is an influence of Job Resources on Psychological Welfare p=0.00. There is an effect of Stress Buffering on Health p=0.015. The implications of the stress-buffering model are interventions to increase available social support or to teach people positive attitudes about commitment, control, and challenge.